Pedagogy, politics and philosophy of peace : interrogating peace and peacemaking - Borg, Carmel, ....-; Grech, Michael, ....- (London : Bloomsbury, 2017)
In an age where official and sponsored violence are becoming normalised and conceived of as legitimate tools of peace keeping, a number of leading academics and activists represented in Pedagogy, Politics and Philosophy of Peace interrogate and resist the intensification of the militarisation of civil life and of international relations. Coming from different areas of study, the contributors to this volume discuss peace and critical peace education from a range of perspectives. The nature of peace, myths related to peace, the logistics of peace and peacemaking as well as the relation of peace and pedagogy in the broadest meaning of the term constitute the main themes of the book. The common thread that binds the chapters together is the distinction between genuine/authentic and false peace and the importance of critical reflection on actions that contribute to genuine peace.
Keywords: Geweld - Vrede